1998
DOI: 10.1023/a:1006073305479
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The activities of Na+,K(+)-ATPase in plasma membrane, of cytosolic enzymes and of glutamate dehydrogenase (GlGD) in mitochondria were measured in leukocytes (WBC) from dogs and cats to clarify the differences in energy metabolism in these cells. Feline WBC had significantly higher activities of hexokinase (HK), pyruvate kinase (PK) and LDH with pyruvate as substrate than did canine WBC. Canine WBC had significantly higher activities of glucokinase (GK) and GlDH than did feline WBC. Feline WBC had unique charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…WO 3 thin films have been prepared by various methods including sputtering [5], chemical vapor deposition [6], Sol-Gel method [7], etc. Magnetron sputtering method is the most popular technique owing to its high depositing rate, high ion energy, low working temperature and better reproducibility.…”
Section: Introductionmentioning
confidence: 99%
“…WO 3 thin films have been prepared by various methods including sputtering [5], chemical vapor deposition [6], Sol-Gel method [7], etc. Magnetron sputtering method is the most popular technique owing to its high depositing rate, high ion energy, low working temperature and better reproducibility.…”
Section: Introductionmentioning
confidence: 99%
“…Sci. 65(11): 1241-1243, 2003 It has been reported that activities of enzymes related to energy metabolism including ATP production in peripheral leukocytes are very variable in animal species [23,24]. In particular, activities of enzymes in the malate-aspartate shuttle, which has a very important role in the transfer from cytosolic NADH to mitochondrial NADH [13], change remarkably according to variation in energy metabolism of animals [2].…”
mentioning
confidence: 99%
“…Leukocytes were isolated by centrifugation with a lymphocyte-isolating solution (ICN Biochemical Inc., Aurora, OH, U.S.A.). Cytosolic and mitochondrial fractions of leukocytes were prepared by the method described previously [23]. The activities of the enzymes were measured by using reported methods: lactate dehydrogenase [11], malate dehydrogenase [7], aspartate aminotransferase (AST) [9] and glutamate dehydrogenase (GLDH) [18].…”
mentioning
confidence: 99%
“…Cytosolic NADH is transferred into mitochondria for oxidation and ATP production through two NADH shuttles, the glycerol phosphate shuttle and the malate-aspartate shuttle [6,10,11]. Activities of some kinds of enzymes in leukocytes (WBC) are considered to reflect the metabolic state in the whole body of dogs and cats [2,16]. In the present study, therefore, activities of enzymes related to the malate-aspartate shuttle, which converts cytosolic NADH into mitochondrial NADH, were measured in WBC from dogs given food supplemented with Echevaria glauca herb powder to investigate the effect of this herb on energy metabolism in animals.…”
mentioning
confidence: 99%
“…The composition ratios of the cells in the isolated WBC were analyzed with a flow cytometer, Cyto Ace-150 (Nihon Bunko, Tokyo, Japan), and the isolated WBC consisted of lymphocytes (55-60%), neutrophils (35-40%) and a few per cent of other cells. Cytosolic and mitochondrial fractions were prepared from the washed WBC by a previously reported method [16]. The activities of enzymes in cytosolic and mitochondrial fractions were measured by previously reported methods: lactate dehydrogenase (LDH) [8], malate dehydrogenase (MDH) [15], aspartate aminotransferase(AST) [13], and glutamate dehydrogenase (GLDH) [14].…”
mentioning
confidence: 99%